Evaluation of Mass Cytometry in the Clinical Laboratory. Issue 4 (7th June 2019) - Ravkov, Eugene V.; Charlton, Cheryl M.; Barker, Adam P.; Hill, Harry; Peterson, Lisa K.; Slev, Patricia; Tebo, Anne; Voelkerding, Karl V.; Wittwer, Carl T.; Heikal, Nahla; Delgado, Julio C.; Lázár‐Molnár, Eszter; et al.
Abstract : Background: Mass cytometry can differentiate more channels than conventional flow cytometry. However, for clinical use, standardization and agreement with well‐established methods is paramount. We compared mass cytometry to standard clinical flow cytometry. Methods: Mass and flow cytometry were performed in parallel on peripheral blood samples from 25 healthy individuals. Antibody staining was performed on the same samples at the same time, and analyzed for granulocyte, monocyte, lymphocyte, T, B, NK, CD4 and CD8 percentages. Validation parameters included comparison to flow cytometry, inter‐ and intra‐assay precision and establishment of reference intervals. Results: There was a positive correlation between mass and flow cytometry for the eight populations studied ( R 2 between 0.26 and 0.97). Slopes of the best‐fit lines varied from 0.50 to 1.21 (fluorescence/mass). No significant differences in variance were found ( F ‐test, P  > 0.05). However, paired t ‐tests were significantly different for four of the eight markers (granulocytes, NK cells, T cells and CD4 cells), resulting in different reference intervals. Signal intensities were correlated for monocytes, lymphocytes, T, CD4 and CD8 cells ( R 2 = 0.41–0.57). The mass cytometry intra‐assay precisions were 0.7–8.5% and inter‐assay precisions 1.5–13.8%. Conclusion: Mass and flow cytometry evaluations of whole blood for major cell populations correlate with similar precision and signal intensity. However, for clinical use, separate reference interval studies are required. Cell population identification should rely on gating strategies that take advantage of the characteristics offered by each method. © 2019 International Clinical Cytometry Society